Impact of Covid-19 Pandemic on DHL Delivery Service - Baliyan, Meenu; Gupta, Shashi; Yinjin, Janice Loh; Kee, Daisy Mui Hung; Binti Abu Habsah, Intan Lyana; Zetian, He; Ke, He; Aggarwal, Juhi (International Journal of Tourism and Hospitality in Asia Pasific, 2022)
The COVID-19 pandemic lockdown in the entire world has significantly affected shopping behavior. This study has tried to survey the delivery services provided by DHL which is a world-leading logistics company that provides services from domestic and international parcel delivery. The COVID-19 pandemic has spiked demand for DHL e-commerce and warehouse space due to abnormality within the global supply chain and ensures non-interruption of production. This paper aims to analyze the impact of the COVID-19 pandemic on the DHL Delivery Service. This research would be conducted by gathering secondary data from DHL’s website and several statistical findings. Besides, quantitative analysis researchers would be using primary data. Further study will be carried out by collecting primary data through a questionnaire. A questionnaire survey among e-commerce customers towards their experiences will be used for data collection with an online survey. Researchers tried to reveal the delivery company services. This study provides DHL with valuable insights and guidance on the impact of the COVID-19 pandemic, leading to improved consumer intention.